Shear Strength and Compression Coefficient for Conditioned Sand Subjected to Earth Chamber Stress Levels - Yi Yang; Xinggao Li; Xingchun Li (Advances in Materials Science and Engineering)
Ground conditioning agents are often needed when performing earth pressure balance shield tunneling in sand soils due to its high internal friction, low plastic ductility, and low compressibility. In this work, vane shear and compression tests for standard sand were performed using a homemade test device, and three types of conditioning agents composed of foam, bentonite slurry, and polymer were used in the tests. The effects of the agents on shear strength and compressibility of the conditioned soils were investigated under a typical earth chamber stress level as high as 2 bar. The measured results show that foam does better in reducing shear strength and improving the compressibility of the conditioned soils than bentonite slurry and polymer. Significant increases in the compressibility of foam-conditioned soils can be achieved using foam, and the shear strength of the conditioned sand can be decreased by more than 30% with an initial injection ratio of 40% foam. The bentonite- and polymer-conditioned sands have similar compressibility. The HPMC (hydroxypropyl methylcellulose) polymer does better in decreasing the shear strength of the conditioned soils than other liquid soil conditioners. The influences of the device shear rate on the shear strength of the conditioned soils are also presented.